Influence of polyvascular disease on cardiovascular event rates: insights from the REACH Registry - Suárez Fernández, Carmen; Zeymer, Uwe; Limbourg, Tobias; Baumgartner, Iris; Cacoub, Patrice; Poldermans, Don; Röther, Joachim; Bhatt, Deepak L; Steg, Ph. Gabriel (Vascular medicine, 2010)
Cardiovascular event rates have been shown to increase substantially with the number of symptomatic disease locations. We sought to assess the risk profile, management and subsequent event rates of polyvascular disease patients. Consecutive outpatients were assessed for atherosclerotic risk factors and medications in the REACH Registry. A total of 19,117 symptomatic patients in Europe completed a 2-year follow-up: 77.2% with single arterial bed disease (coronary artery or cerebrovascular or peripheral arterial disease) and 22.8% with polyvascular disease (≥ 1 disease location). Polyvascular disease patients were older (68.5 ± 9.4 vs 66.3 ± 9.9 years, p < 0.0001), more often current or former smokers (64.9% vs 58.7%, p < 0.0001), and more often suffered from hypertension (59.5% vs 46.6%, p < 0.0001) and diabetes (34.5% vs 25.9%, p < 0.0001) than single arterial bed disease patients. Despite more intense medical therapy, risk factors (smoking, hypertension, low fasting glucose, and low fasting total cholesterol) were less often controlled in polyvascular disease patients. This was associated with substantially more events over 2 years compared with single arterial bed disease patients (cMACCE [cardiovascular death/non-fatal stroke/non-fatal MI] odds ratio, 1.63 [95% CI, 1.45—1.83], p < 0.0001). In conclusion, polyvascular disease patients have more cardiovascular risk factors, and the prognosis for these patients is significantly worse than for patients with single arterial bed disease. This suggests a need to improve detection and consequent medical treatment of polyvascular disease.